New Nitro-Laterally Substituted Azomethine Derivatives; Synthesis, Mesomorphic and Computational Characterizations - Mohamed A. El-atawy; Magdi M. Naoum; Salma A. Al-Zahrani; Hoda A. Ahmed (Molecules, 2021)
Two new homologues series, based on two rings of the azomethine central group bearing the terminal alkoxy group of various chain lengths, were prepared. The alkoxy chain length varied between 6 and 16 carbons. The other terminal wing in the first series was the F atom, and the compound is named N-4-florobenzylidene-4-(alkoxy)benzenamine (In). The second group of compounds included a lateral NO2 substituent in addition to the terminal F atom, named N-(4-fluoro-3-nitrobenzylidene)-4-(alkyloxy)aniline (IIn). Mesomorphic and optical properties were carried out via differential scanning calorimetry (DSC) and polarized optical microscopy (POM). Elemental analyses, FT-IR, and NMR spectroscopy were carried out to elucidate the molecular structures of the synthesized groups. Mesomorphic investigations indicated that all the synthesized homologues (In) were monomorphic, possessing the smectic A (SmA) phase monotropically, while the second group (IIn) members were non-mesomorphic. The experimental data indicated that the formation of the mesophase is affected by the protrusion of the lateral nitro group. The disruption of the mesophase in the second group was attributed to the increase of its molecular width, which affects its lateral intermolecular interactions. The computational simulations were in agreement with the experimental data. On the other hand, the location of NO2 group within the molecular geometry increased the melting temperature of the molecule, and thus, affected their thermal and physical properties. By discussing the estimated parameters, it was found that the molecular architecture, the dipole moment, and the polarizability of the investigated compounds are highly affected by the electronic nature and position of the terminal and lateral substituents as well as their volumes.